Antidepressant mechanism of ketamine: perspective from preclinical studies - Scheuing, Lisa; Chiu, Chi-Tso; Liao, Hsiao-Mei; Chuang, De-Maw (Frontiers in Neuroscience, 2015)
A debilitating mental disorder, major depressive disorder is a leading cause of global disease burden. Existing antidepressant drugs are not adequate for the majority of depressed patients, and large clinical studies have demonstrated their limited efficacy and slow response onset. Growing evidence of low-dose ketamine’s rapid and potent antidepressant effects offers strong potential for future antidepressant agents. However, ketamine has considerable drawbacks such as its abuse potential, psychomimetic effects, and increased oxidative stress in the brain, thus limiting its widespread clinical use. To develop superior antidepressant drugs, it is crucial to better understand ketamine’s antidepressant mechanism of action. Recent preclinical studies indicate that ketamine’s antidepressant mechanism involves mammalian target of rapamycin pathway activation and subsequent synaptogenesis in the prefrontal cortex, as well as glycogen synthase kinase-3 beta (GSK-3B) inactivation. Adjunct GSK-3B inhibitors, such as lithium, can enhance ketamine’s efficacy by augmenting and prolonging its antidepressant effects. Given the potential for depressive relapses, lithium in addition to ketamine is a promising solution for this clinical issue.